2016
DOI: 10.18235/0000428
|View full text |Cite
|
Sign up to set email alerts
|

Violent Crime in Latin American Cities

Abstract: Any dispute related to the use of the works of the IDB that cannot be settled amicably shall be submitted to arbitration pursuant to the UNCITRAL rules. The use of the IDB's name for any purpose other than for attribution, and the use of IDB's logo shall be subject to a separate written license agreement between the IDB and the user and is not authorized as part of this CC-IGO license. Note that link provided above includes additional terms and conditions of the license.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 58 publications
0
9
0
1
Order By: Relevance
“…However, over the last twenty years, there have been many improvements in inequality and income distribution across Latin America (Ocampo and Vallejo 2012). Over this period, the Gini coefficient (a measure of inequality) reduced by almost ten percent from 0.542 to 0.486 in the region, yet homicide rates increased (Bergman 2018;Vilalta et al 2016). Examined more specifically in relation to certain countries in the region, Brazil and Mexico have experienced periods of economic growth and decreasing income inequality, but high levels of homicide have persisted.…”
Section: Qualitative Review: Factors Explaining High Homicide Levels-a Latin America Focusmentioning
confidence: 99%
“…However, over the last twenty years, there have been many improvements in inequality and income distribution across Latin America (Ocampo and Vallejo 2012). Over this period, the Gini coefficient (a measure of inequality) reduced by almost ten percent from 0.542 to 0.486 in the region, yet homicide rates increased (Bergman 2018;Vilalta et al 2016). Examined more specifically in relation to certain countries in the region, Brazil and Mexico have experienced periods of economic growth and decreasing income inequality, but high levels of homicide have persisted.…”
Section: Qualitative Review: Factors Explaining High Homicide Levels-a Latin America Focusmentioning
confidence: 99%
“…Previous studies have shown that signs of disorder are correlated with concentrated disadvantage (Gau and Pratt, 2010;Sampson and Raudenbush, 2004;Wilcox et al, 2004). Measures of neighborhood disadvantage (e.g., poverty, unemployment, family income, literacy, welfare) and neighborhood instability (e.g., residential mobility and divorciality) have been associated to spatial variations of homicide (Akins, Rumbaut, and Stansfield, 2009;Barata et al, 1998;Berezin et al, 2017;Boessen and Hipp, 2015;Ferrandino, 2018;Hannon, 2005;Kubrin and Weitzer, 2003;Larsen et al, 2017;Mancik, Parker, and Williams, 2018;Mares, 2010;Nieuwbeerta et al, 2008;Ousey, 2006;Parker and McCall, 1999;Pereira, Mota, and Andresen, 2017;Santos, Barcellos, and Sacarvalho, 2006;Strom and MacDonald, 2016;Suresh and Vito, 2009;Vilalta, Castillo, and Torres, 2016;Vilalta and Fondevila, 2019;Vilalta and Muggah, 2014).…”
Section: Homicide and Concentrated Disadvantagementioning
confidence: 99%
“…Entertainment venues, bars, and restaurants correlate with more homicide (Ceccato, Haining, and Kahn, 2007;Henderson et al, 2005;Hohl et al, 2017;Sparks, 2011;Swart, Seedat, and Nel, 2018;Vilalta, Castillo, and Torres, 2016). One study though, focusing on the "nighttime economy" of Australia, finds that homicides are not concentrated around drinking and leisure districts, but evenly spread out across suburban, small town, and rural and regional areas (Tomsen and Payne, 2016).…”
Section: Homicide and Land-use Characteristicsmentioning
confidence: 99%
“…En Delitos violentos en ciudades de América Latina (Vilalta et al, 2016), el Banco Interamericano de Desarrollo señala cuatro factores estructurales que contribuyen a la violencia en las ciudades latinoamericanas. Los mismos son: i) penurias económicas; ii) inestabilidad residencial; iii) desintegración familiar y; iv) consumo de alcohol.…”
Section: * * *unclassified